Analisis Pemahaman Pajak Penghasilan Dan Sanksi Pajak Terhadap Pelaksanaan Wajib Pajak Orang Pribadi (WP OP) Pegawai - Muhammad Falhan; Hafsah Hafsah; Zulia Hanum (Politeknik Ganesha Medan, 2023)
Non-compliance in the implementation of taxes by individual taxpayers for employees will lead to a tax sanction, besides knowledge is also a factor in the non-compliance so that this is a phenomenon in this study. This research generally aims to find out how the understanding of income tax on individual taxpayers (WP OP) employees and how the conditions of understanding and tax sanctions on individual taxpayers (WP OP) employees. The research methodology used is a descriptive qualitative approach with a case study research approach. Descriptive qualitative research is a type of research by analyzing in depth and providing an overview of the research results. The method of data collection was done through interviews with several informants, namely several employees on the object of research. Then analyzed using descriptive analysis method, so as to obtain an overview of the object factually, accurately, and systematically. The result of this research is the understanding of income tax and tax sanctions. mandatory individual (WP OP) employees, namely not understanding income tax. Meanwhile, with tax sanctions, employees only know but do not understand so that many violate sanctions due to lack of knowledge about tax sanctions. The conclusion of this study is the understanding of income tax and tax sanctions. mandatory personal (WP OP) the employee is still minimal. They still do not know that they are individual taxpayers with the category of non-permanent employees and at what rate to pay and how to pay it.